The Optimization of Scheduling Development Process to Cultivate Nile Tilapia By Using Pert-Cpm Method - Rasdiana S Ma’bud; Fauziah Nurhamiddin (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The problem in this research is how long thetime and costs in doing the development of cultivationthe Nile Tilapia by using PERT-CTM method and how to determine the optimal path for the work of project development of NileTilapia cultivation. This research was conducted in Togawa village, district of south Galela on July until August 2019. The source of data got in this study from primary data that is through direct observation to fish pond farmers who were the object of research as well as conducting interview with the owners of fish pond of Nile Tilapia, and alsoto collect the documentation of cultivation process of Nile Tilapia. The result of calculation using PERT – CTM method obtained that the optimization of the scheduling the development process of Nile Tilapia cultivation in period of 134 days with a fee of Rp. 21.700.000.